Dissolved organic matter dynamics in surface waters affected by oil spill pollution: Results from the Serious Game exercise. (November 2016) - Gonnelli, M; Galletti, Y; Marchetti, E; Mercadante, L; Retelletti Brogi, S; Ribotti, A; Sorgente, R; Vestri, S; Santinelli, C
Abstract: Dissolved organic carbon (DOC), chromophoric and fluorescent dissolved organic matter (CDOM and FDOM, respectively) surface distribution was studied during the Serious Game exercise carried out in the Eastern Ligurian Sea, where an oil spill was localized by using satellite images and models. This paper reports the first DOC, CDOM and FDOM data for this area together with an evaluation of fluorescence as a fast and inexpensive tool for early oil spill detection in marine waters. The samples collected in the oil spill showed a fluorescence intensity markedly higher (~5 fold) than all the other samples. The excitation–emission matrixes, coupled with parallel factor analysis (PARAFAC), allowed for the identification in the FDOM pool of a mixture of polycyclic aromatic hydrocarbons, humic-like and protein-like fluorophores.